Criticism of the article Říčan J. et al. – Comparison of the quality of the teacher made tests with achievement tests and their influence on the success of pupils: case study. Scientia in educatione, 12(2), 2021 - Novotný, Petr (Scientia in educatione, 2022)
This is the author's view about an article published in Scientia in educatione in 2021. He considers the structure of the article, its content and scientific quality inappropriate and brings forward artuments and criticism to support his claims. The critical notes are preented in a chronological order.